Urinary and Serum N-acetyl B-Glucosaminidase as Biomarkers of Albuminuria in Patients with Type 2 Diabetes (Medico Legal Update, 2020)
Background: Diabetic nephropathy is a serious kidney-related complication of type 1 diabetes and type 2 diabetes. It is also called diabetic kidney disease. About 25% of people with diabetes eventually develop kidney disease. The enzyme N-Acetyl-?-glucosaminidase (NAG) (EC: 3.2.1.30) is one of lysosomal acid hydrolases enzyme present in many body tissues with a high molecular weight (~ 140 kDa). It breaks chemical bonds of glycoside and amino sugars which form structural components in many tissues. Different pieces of cells need to be degraded and disposed of, including the cell membrane. Method: By using ELISA kit, we measured urine and serum level of N-acetyl B-Glucosaminidase in 30 patients diabetes with Microalbuminuria: ACR: 30 mg/g with 30 healthy volunteers enlisted as normal controls. Result: Urine concentration of NAG in macro and micro- groups was comparable (13.23±1.04 ng/mL and 13.1±1.46 ng/mL, respectively) with no significant difference, while both groups showed highly significant difference compared with normo- group (5.15±2.11 ng/mL) On the other hand, serum concentration of NAG in normo- micro- and macroabluminuria was 1.2±0.3 ng/mL, 2.5±0.58 ng/mL and 3.2±0.77 ng/mL, respectively, with highly significant differences between the three groups. Conclusion: N-Acetyl-?-Glucosaminidase: the present study, diabetic nephropathy was associated with elevated urinary and serum NAG values compared to a control group. This increase in NAG was parallel to the severity of renal involvement with a characteristic increasing trend was observed among the study groups regarding albuminuria